Increased Transparency and Resource Prioritization for the Management of Pollutants From Wastewater Treatment Plants: A National Perspective From Australia - Rohmana, Qurratu A’Yunin; Fischer, Andrew M.; Cumming, John; Blackwell, Boyd D.; Gemmill, John (Frontiers in Marine Science, 2020)
With increasing human populations in coastal regions, there is growing concern over the quality of wastewater treatment plant (WTPs) discharge and its impacts on coastal biodiversity, recreational amenities and human health. In Australia, the current system of WTP monitoring and reporting varies across states and jurisdictions leading to a lack of data transparency and accountability, leading to a reduced ability to comprehensively assess regional and national scale biodiversity impacts and health risks. The National Outfall Database (NOD) was developed to provide a centralized spatial data management system for sharing and communicating comprehensive, national-scale WTP pollutant data. This research describes the structure of the NOD and through self-organizing maps and principal component analysis, provides a comprehensive, national-scale analysis of WTP effluent. Such a broad understanding of the constituents and level of pollutants in coastal WTP effluent within a public database provides for improved transparency and accountability and an opportunity to evaluate health risks and develop national water quality standards.